Convallatoxin ameliorates fibroblast-like synoviocytes-mediated synovial inflammation and joint destruction in rheumatoid arthritis by targeting IDH1 - Suling Liu; Huijuan Hu; Yu Kuang; Simin Chen; Kai Sun; Chenxi Peng; Ruiru Li; Fan Su; Liuqin Liang; Qian Qiu; Youjun Xiao; Hanshi Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Solution-processed high-performance green perovskite QLEDs enabled by pseudohalide passivation and photo-triggered ligand crosslinking - Ruiru Liu; Mingjing Li; Xiao Wang; Fei Zheng; Zhenfu Zhao; Ziyang Hu (Chemical Engineering Journal, 2025)

“One stone two birds” strategy for sustainable water purification: Bifunctional photothermic-catalytic manganese oxide/carbon composites enabling solar evaporation, seawater desalination and periodate activation - Jing Jiang; Xiaojing Lai; Yu Fang; Ruiru Yang; Xinyu Zheng; Song Tian; Fenfen Yang; Aike Liu; Lunhong Ai (Desalination, 2025)

The immune responses elicited by six recombinant antigens of Mycoplasma hyopneumoniae in mice - Shiyang Li; Ruiru Yin; Qiyan Xiong; Maojun Liu; Jia Wang; Zhenzhen Zhang; Guoqing Shao; Zhibang Deng; Zhixin Feng; Yanfei Yu (Veterinary Microbiology, 2024)

Photothermic-catalytic bifunctionality of boron-doped molybdenum disulfide nanosheets enabling simultaneous solar evaporation and antibiotic destruction - Mingming Chang; Ruiru Yang; Xiaojing Lai; Xinzhi Wang; Aike Liu; Jing Jiang (Chemical Engineering Journal, 2024)

Correction to: Identification and map‑based cloning of an EMS‑induced mutation in wheat gene TaSP1 related to spike architecture - Lin Zhang; Huidan Zhou; Xian Fu; Niuniu Zhou; Mengjie Liu; Shenglong Bai; Xinpeng Zhao; Ruiru Cheng; Suoping Li; Dale Zhang (Theoretical and Applied Genetics, 2024)

Identification and map-based cloning of an EMS-induced mutation in wheat gene TaSP1 related to spike architecture - Lin Zhang; Huidan Zhou; Xian Fu; Niuniu Zhou; Mengjie Liu; Shenglong Bai; Xinpeng Zhao; Ruiru Cheng; Suoping Li; Dale Zhang (Theoretical and Applied Genetics, 2024)

Coordination of economics spectra in leaf, stem and root within the genus Artemisia along a large environmental gradient in China - Rong Liu; Xuejun Yang; Ruiru Gao; Zhenying Huang; Johannes H. C. Cornelissen (Global Ecology and Biogeography, 2023)
Aim The plant economics spectrum provides a fundamental framework for understanding functional trait variation along environmental gradients. However, it is unclear whether there is a general whole‐plant economics spectrum across organs at the finer taxonomic scale (e.g. within genera), and if there is, which factors affect the trait coordination of the different organs. Here, we examined whether resource economics spectra of different organs (i.e. leaf, stem and root) can be integrated at the whole‐plant level within a single genus, and how environment, intraspecific variation and taxonomic scale shape the whole‐plant spectrum. Location China. Time period 2018. Major taxa studied Artemisia . Methods We sampled 1,022 individuals of 62 Artemisia species in central and eastern China to test trait coordination patterns from organ to whole‐plant level. From the resource economics spectrum perspective, 15 traits were chosen to represent the trade‐off between structural and nutrient investments, including organs’ C, N, P and dry matter content, specific leaf area, specific stem length and specific root length. Results Pairwise trait correlations and the trade‐off patterns along the resource economic axis were consistent at both organ and whole‐plant levels. Environmental gradients did not strongly affect the correlations among leaf, stem and root economics spectra, that is, the intraspecific variation weakened but did not mask this coordination. Taxonomic scale did not affect the degree of trait coordination as the genus‐wide whole‐plant economics spectrum also emerged within each of the three subgenera. Main conclusions Our results support the hypothesis that the coordination of economics spectra across organs forms a whole‐plant economics spectrum representing a ‘fast–slow’ resource management strategy, which is robust to recent evolution (genotypic variation, even for species within a single genus) and present‐day environmental variation. Further studies should elucidate in which circumstances or phylogenetic branches the coordinated pattern found for Artemisia is representative of other widely distributed genera.

Net plant interactions are highly variable and weakly dependent on climate at the global scale - Xuejun Yang; Lorena Gómez‐Aparicio; Christopher J. Lortie; Miguel Verdú; Lohengrin A. Cavieres; Zhenying Huang; Ruiru Gao; Rong Liu; Yonglan Zhao; Johannes H. C. Cornelissen (Ecology Letters, 2022)
Although plant–plant interactions (i.e. competition and facilitation) have long been recognised as key drivers of plant community composition and dynamics, their global patterns and relationships with climate have remained unclear. Here, we assembled a global database of 10,502 pairs of empirical data from the literature to address the patterns of and climatic effects on the net outcome of plant interactions in natural communities. We found that plant interactions varied among plant performance indicators, interaction types and biomes, yet competition occurred more frequently than facilitation in plant communities worldwide. Unexpectedly, plant interactions showed weak latitudinal pattern and were weakly related to climate. Our study provides a global comprehensive overview of plant interactions, highlighting competition as a fundamental mechanism structuring plant communities worldwide. We suggest that further investigations should focus more on local factors (e.g. microclimate, soil and disturbance) than on macroclimate to identify key environmental determinants of interactions in plant communities.

Effects of rainfall pattern on the growth and fecundity of a dominant dune annual in a semi-arid ecosystem - Ruiru Gao; Xuejun Yang; Guofang Liu; Zhenying Huang; Jeffrey L. Walck (Plant and Soil, 2015)